A Literature Review: Understanding TNF and IL-1 of the Main Cause of Thorombo-occlusive in Lucio’s Phenomenon - Erald Giovanny Hasiholan Simatupang; Ulfa Pratiwi; Hayuningrat Odyssey Saint; Dhea Ivanka (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
Last year, it was 0.5 out of every 10,000 people, but now it has increased. Lucio's Leprosy, also known as Leprosy Bonita, is a very uncommon type of serious leprosy. The Lucio phenomenon is a severe reaction that can occur in individuals with Lucio's leprosy. It causes a skin condition called "necrotizing erythema". This study used reliable and important scientific databases like PubMed, ScienceDirect, Google Scholar, as well as official databases from health organizations. These reactions occur in the cells of body's immune system, specifically the T helper 1 cells, in response to antigens from mycobacteria. Research has shown that certain substances produced by Th1 cells, such as IL-1?, TNF-?, IL-2, and IFN-?, are very important. High amounts of TNF-?, soluble IL-2 receptors, and adhesion molecules show how serious the local inflammation is. Patients with a mild form of leprosy who are experiencing a specific type of immune response have higher levels of a molecule called TNF-? in their nerves and skin. Type 1 reactions are caused by certain types of immune cells called Th1 lymphocytes. The WHO said it's important to make sure patients and communities know about leprosy so they can get help on their own. They think this is a very important part of their plan to fight leprosy worldwide.